И. А. Бунин-редактор: Об окончательном (каноническом) тексте повести Л. Ф. Зурова «Кадет» [Bunin the Editor: What Should be Seen as the Critical Text of Leonid Zurov’s Short Novel “Kadet”?] - Belobrovtseva, Irina (Slavica Revalensia, 2014)
The Leeds Russian Archive in the University of Leeds holds an intriguing item:a copy of the first edition of Leonid Zurov’s povest’ (short novel) “Kadet” (1928), partially edited by the writer’s older friend Ivan Bunin. How did Bunin edit the text? What did he alter and why? And what should be seen as the final—the critical—text of the povest’? The article answers these questions and also addresses the question of final authorial intent.